Faktor-Faktor Penentu Tingkat Kemampuan Petani Dalam Mengelola Lahan Marjinal Kasus di Desa Karangmaja, Kecamatan Karanggayam, Kabupaten Kebumen, Jawa Tengah) - Tanti Kustiari; Djoko Susanto; Sumardjo Sumardjo; Ismail Pulungan (Jurnal Penyuluhan, 2006)
The objectives of the study are: (1) To explore the capability of the farmers to carry out land-use of marginal or dry land; (2) To analyse factors which relate to farmers’ capability in managing marginal land. The study was carried out in Karangmaja village, sub District of Karanggayam, the District of Kebumen Central Java. As many 100 farmers were selected by proportion random sampling as respondents. Data were analyzed using Rank Spearman non parametric method. Important results show that the capability of the farmers to manage marginal land is categorized as sedentary. Internal factors such as: motivation and participation of the farmers to joint farmers’ group, interaction which information sources and dependency on land have significant correlation to the capability of the farmers to manage marginal land.